2008
DOI: 10.1111/j.1574-6968.2008.01351.x
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of the pyruvate dehydrogenase E1α subunit, inStreptococcus mutansacid tolerance

Abstract: Streptococcus mutans, an etiological agent of dental caries, is a normal inhabitant of dental plaque. Two main virulence factors of S. mutans are acidogenicity and aciduricity - the ability to produce acid and survive at low pH, respectively. Metabolic processes, including the catabolism of pyruvate, are finely regulated following acid exposure in S. mutans. Proteome analysis of the S. mutans acid response has shown pyruvate dehydrogenase A (PdhA) is upregulated. PdhA is the E1alphasubunit of the four-enzyme p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…Sequence analysis of the cloned insert revealed that these fragments corresponded to portions of SMU.402 and SMU.1278 encoding a pyruvate formate-lyase (PFL) and a putative phosphoglycolate phosphatase, respectively. Although work previously done in S. mutans has shown that PFL was responsible for pyruvate heterofermentation under anaerobic conditions (25), it is still unclear how this may relate to persistence.…”
Section: Figmentioning
confidence: 93%
“…Sequence analysis of the cloned insert revealed that these fragments corresponded to portions of SMU.402 and SMU.1278 encoding a pyruvate formate-lyase (PFL) and a putative phosphoglycolate phosphatase, respectively. Although work previously done in S. mutans has shown that PFL was responsible for pyruvate heterofermentation under anaerobic conditions (25), it is still unclear how this may relate to persistence.…”
Section: Figmentioning
confidence: 93%
“…increased glycolytic flux of triose phosphates, threonine/glycine catabolism and acetone breakdown . However, regardless of the pathway of methylglyoxal formation, the detoxification is exclusively dependent on cellular glyoxalases (Ferguson et al, 1995;Korithoski et al, 2007;Ozyamak et al, 2010). The presence of a lactoylglutathione lyase (a putative glyoxalase I) gene in S. enterica serovar Typhimurium, Enteritidis, Gallinarum and other non-typhoidal serovars, but absence in typhoidal serovars might be indicative of host-specific acquisition of virulence determinants and metabolic requirements (Charles et al, 2009;Pujol et al, 2005;Rathman et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Methylglyoxal, a toxic byproduct of many physiological reactions (Chauhan & Madhubala, 2009;Kim et al, 2012;Korithoski et al, 2007;MacLean et al, 1998;Yadav et al, 2005), arises primarily through various metabolic pathways, e.g. increased glycolytic flux of triose phosphates, threonine/glycine catabolism and acetone breakdown .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations